Novel heat-insulating, anti-corrosion and self-repairing cement-based material for subsea tunnel

By adding the ion complexing agent triethanolamine, nanosilicon dioxide and expanded perlite particles to the cement-based materials of the sea tunnel, the structural damage problem caused by chloride ion penetration and temperature differences in extreme environments is solved, and high strength, heat insulation, corrosion and self-healing effects are achieved.

CN119528513APending Publication Date: 2025-02-28NORTHEAST FORESTRY UNIV
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411724168.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-28
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

The cement-based materials of the undersea tunnel are susceptible to structural damage caused by chloride ion penetration and temperature differences in extreme environments, and are difficult to effectively maintain, resulting in threats to structural durability and safety.

Method used

A new cement-based material is adopted, including the ion complexing agent triethanolamine, nanosilicon dioxide and expanded perlite particles. The expanded perlite particles aggregate is processed through shell wrapping and secondary stirring to enhance the material's anti-seepage performance and self-healing ability.

Benefits of technology

This material can effectively reduce chloride ion penetration, enhance the durability and safety of the structure, realize self-repair, and reduce maintenance frequency and cost.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119528513A_ABST
    Figure CN119528513A_ABST
Patent Text Reader

Abstract

The invention discloses a novel heat-insulating, anti-corrosion and self-repairing cement-based material for a subsea tunnel. The novel heat-insulating, anti-corrosion and self-repairing cement-based material comprises the following parts: an ion complexing agent triethanolamine, ordinary Portland cement, nano silicon dioxide, expanded perlite particles and the like. Wherein the ion complexing agent triethanolamine'captures' seawater ions, so that precipitates are formed in cracks, the cracks are filled, and the structural integrity is recovered. In addition, nano silicon dioxide is used for reducing permeation of chloride ions and other harmful substances so as to prevent the cement-based material from decaying and reacting with cement hydration products to form a more compact microstructure, so that the compactness and durability of the cement-based material are improved. The expanded perlite particles are used for reducing the influence of the external temperature on the interior of the cement-based material and the tunnel space, maintaining the temperature stability in the subsea tunnel is facilitated, energy consumption is reduced, and the durability and safety of the structure are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of new multifunctional materials, and mainly relates to a new high-strength heat-insulating, corrosion-resistant and self-repairing cement-based material for submarine tunnels. Background Art

[0002] The environmental conditions of submarine tunnels are very special and harsh, so the maintenance of submarine tunnels is more difficult than that of ground buildings. Subsea tunnels must be able to withstand huge water pressure. At a depth of 100 meters on the seabed, the top of the tunnel is subjected to a water pressure of about 10.1 MPa per square meter. In addition, the design of submarine tunnels also needs to consider factors such as soil pressure, wave action, and earthquake action. These factors can cause voids and microcracks on the surface of cement-based materials. In addition, chloride ions in seawater can penetrate into the interior of cement-based materials through the pores and microcracks generated by the above factors. When steel bars are in cement-based materials, they are often protected by a passivation film, which is produced in an alkaline environment formed by calcium hydroxide. This film can prevent steel bars from contacting oxygen and moisture, and play an anti-corrosion role. However, when the chloride ion concentration exceeds the critical value, the chloride ions will replace the hydroxide ions in the passivation film, thereby destroying the stability of the passivation film. After the passivation film is destroyed, the surface of the steel bars is exposed to oxygen and moisture, and electrochemical corrosion will occur, thereby producing iron hydroxide, i.e., rust products. The volume of the rust product is much larger than the original steel bar volume, and its volume may be 2 to 6 times that of the original iron. This volume expansion will exert huge pressure on the surrounding cement-based materials, resulting in tensile stress inside the cement-based materials. When this tensile stress exceeds the tensile strength of the cement-based materials, the cement-based materials will crack. As the corrosion progresses further, the cracks will expand, eventually leading to the peeling of the protective layer of the cement-based materials. Affecting the bearing capacity and safety of the structure. Cracks and peeling may also accelerate the further penetration of chloride ions, forming a vicious cycle, leading to faster degradation of the structure, with losses ranging from millions to tens of millions of dollars per kilometer.

[0003] In addition, extreme temperature differences can cause damage to tunnel structures. When the warm air inside the tunnel comes into contact with the cold outer wall, condensation may occur, leading to structural corrosion and affecting electrical equipment and traffic safety inside the tunnel. Thermal expansion and contraction can cause stress inside cement-based materials, which can cause cracking of cement-based materials under restraint conditions, microcracks can expand, and the bonding between steel bars and cement-based materials can be damaged, affecting the bearing capacity of the structure and leading to safety risks.

[0004] In order to improve the strength of materials, reduce the difficulty of undersea tunnel maintenance, and reduce the maintenance cost of undersea tunnels, various countries have adopted various measures. For example, regular preventive maintenance, such as cleaning, coating renewal, drainage system inspection, etc., adopt non-destructive testing technologies, such as ultrasonic testing, infrared thermal imaging, etc., to reduce the cost of destructive testing. Develop long-term maintenance plans, allocate resources reasonably, and avoid the high cost of emergency repairs. Use long-term waterproof materials and coatings to reduce water seepage and corrosion problems.

[0005] However, there is currently no means to simultaneously and effectively solve the problems of chloride ion corrosion, large temperature difference between inside and outside, and difficult maintenance in submarine tunnels. Therefore, it is necessary to find an effective solution that can both insulate and reduce the penetration of chloride ions in seawater and achieve self-repair in the submarine environment.

[0006] The invention discloses a new type of heat-insulating, anti-corrosion and self-repairing cement-based material for submarine tunnels, which is composed of ion complexing agent triethanolamine, ordinary silicate cement, nano-silicon dioxide, expanded perlite particles and the like. Among them, the ion complexing agent triethanolamine is used to react with ions in the ocean to generate precipitates to fill the cracks formed and restore the integrity of the structure. In addition, nano-silicon dioxide is used to reduce the penetration of chloride ions and other harmful substances to prevent the corruption of cement-based materials. Expanded perlite particles are used to reduce the impact of external temperature on the interior of cement-based materials and tunnel space, maintain the temperature stability inside the submarine tunnel, and improve the durability and safety of the structure. Summary of the invention

[0007] The present invention aims to solve the problem that the existing submarine tunnels made of cement-based materials have a large temperature difference between the inside and outside and are easily penetrated by chloride ions in seawater, causing structural damage and difficult maintenance. The present invention designs and discloses a new type of heat-insulating, corrosion-resistant and self-repairing cement-based material for submarine tunnels.

[0008] According to some embodiments of the present invention, a new type of heat-insulating, anti-corrosion and self-repairing cement-based material for submarine tunnels is used, and a shelling process and a secondary mixing method are used to treat hydrophobic expanded perlite particle aggregate. First, the perlite is soaked in water for about 5 minutes until it is nearly saturated, and then dried until the surface is dry. Next, the cement and water are mixed and stirred, and the pre-wetted perlite is added and continued to be stirred until the surface of the perlite is completely covered with cement slurry. Finally, the mixture is poured out and left to stand naturally for 6 hours to form a hard shell-wrapped expanded perlite particle aggregate.

[0009] According to some embodiments of the present invention, a new type of heat-insulating, anti-corrosion and self-repairing cement-based material for submarine tunnels is prepared. The ion complexing agent triethanolamine is directly added with the mixing water during the mixing process of the cement paste in an internal manner, which effectively improves the anti-permeability performance of the cracked cement paste sample. The maximum crack width that can be repaired by the sample reaches 400-600μm. The addition of 1.5% of the ion complexing agent triethanolamine will increase the yield stress of the paste, damage the working performance, prolong the final setting time, increase the large pore size and the number of large pores in the hardened paste, and reduce the strength of cement mortar at various ages, which meets or exceeds the technical requirements of existing national standards.

[0010] According to some embodiments of the present invention, a new type of heat-insulating, anti-corrosion and self-repairing cement-based material for submarine tunnels ensures that the nano-silicon dioxide and cement are in a dry state and meet the required specifications and quality requirements. According to the designed ratio, the required mass ratio of nano-silicon dioxide and cement is accurately weighed to be 1:9, and the weighed nano-silicon dioxide and cement are put into a mixer. Start the mixer, use a mechanical stirring method to mix, and dry mix at a low speed for 90 seconds so that the nano-silicon dioxide particles can be evenly dispersed in the cement powder to avoid agglomeration.

[0011] According to some embodiments of the present invention, a new type of heat-insulating, anti-corrosion and self-repairing cement-based material for submarine tunnels is used, and a shelling process and a secondary mixing method are used to treat hydrophobic expanded perlite particle aggregate. First, the perlite is soaked in water for about 5 minutes until it is nearly saturated, and then dried until the surface is dry. Next, the cement and water are mixed and stirred, and the pre-wetted perlite is added and continued to be stirred until the surface of the perlite is completely covered with cement slurry. Finally, the mixture is poured out and left to stand naturally for 6 hours to form a hard shell-wrapped expanded perlite particle aggregate.

[0012] According to some embodiments of the present invention, a new type of heat-insulating, anti-corrosion and self-repairing cement-based material for submarine tunnels is provided, wherein the water-cement ratio of the ordinary silicate cement-based material is 0.34, water is mixed with a high-efficiency water reducer, and stirred evenly with a glass rod. Cement containing nano-silicon dioxide and an aqueous solution containing a high-efficiency water reducer are poured into a stirring pot, stirred at a low speed for 30 seconds, then stirred at a high speed for 150 seconds, and then water with a corresponding water-cement ratio, 1.5% of an ion complexing agent triethanolamine, and expanded perlite particle aggregate wrapped in a hard shell are sequentially added, stirred at a low speed for 30 seconds, and then stirred at a high speed for 90 seconds to make a cement-based material.

[0013] According to some embodiments of the present invention, a new type of heat-insulating, anti-corrosion and self-repairing cement-based material for submarine tunnels can insulate, reduce the penetration of chloride ions in seawater and self-repair. Compared with the prior art, the characteristics of the present invention are:

[0014] (1) A new type of heat-insulating, anti-corrosion and self-repairing cement-based material for undersea tunnels has higher strength than normal sewage pipe cement-based materials and can self-repair, thereby reducing the frequency of undersea tunnel maintenance.

[0015] (2) A new type of thermal insulation, corrosion resistance and self-healing cement-based material for submarine tunnels can reduce heat exchange and chloride ion penetration corrosion between the submarine environment and the tunnel interior, thereby increasing the durability and stability of the structure. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 This is a schematic diagram of the principle of a new type of heat-insulating, anti-corrosion and self-repairing cement-based material used in submarine tunnels in the implementation of the present invention.

[0017] Item numbers in the figure: 1- a schematic concrete sample of a new type of heat-insulating, anti-corrosive and self-repairing cement-based material for undersea tunnels, 1-1 expanded perlite particles, 1-2 ion complexing agent triethanolamine, 1-3 nano-silicon dioxide, 1-4 ordinary Portland cement.

[0018] Figure 2 This is a schematic diagram of an enlarged electron microscope of expanded perlite particles in a new type of heat-insulating, corrosion-resistant and self-repairing cement-based material used in submarine tunnels in the implementation of the present invention.

[0019] Figure 3 This is a schematic diagram of an enlarged electron microscope image of nano-silicon dioxide in a new type of heat-insulating, corrosion-resistant and self-repairing cement-based material used in submarine tunnels in the implementation of the present invention.

[0020] Figure 4 This is a schematic diagram of the distribution of various elements in the EDS energy spectrum of an electron microscope of a new type of heat-insulating, anti-corrosion and self-repairing cement-based material used in submarine tunnels in the implementation of the present invention.

[0021] Figure 5 This is a total spectrum of the distribution of each element in an electron microscope of a new type of heat-insulating, anti-corrosion and self-repairing cement-based material used in submarine tunnels in the implementation of the present invention. DETAILED DESCRIPTION

[0022] The embodiments of the present invention are described in detail below, and examples of the embodiments are shown in the accompanying drawings, wherein the same or similar reference numerals throughout represent the same or similar elements or elements with the same or similar functions. The embodiments described below with reference to the accompanying drawings are exemplary and are only used to explain the present invention, and cannot be understood as limitations on the present invention. The technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, not all embodiments. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0023] The present invention is further described in detail below in conjunction with the accompanying drawings:

[0024] Combination Figure 1 The novel heat-insulating, anti-corrosion and self-repairing cement-based material for submarine tunnels disclosed in the present invention is made of the following raw materials in percentage by weight: expanded perlite particles (1-1) as aggregate are added in an amount of 90% of the weight of cement, the proportion of ion complexing agent triethanolamine (1-2) is 1.5% to 2%, and the proportion of nano-silicon dioxide (1-3) is 2% to 8%.

[0025] Figure 2 This is a schematic diagram of an electron microscope magnification of expanded perlite particles in a new type of heat-insulating, anti-corrosion and self-repairing cement-based material for submarine tunnels in the implementation of the present invention. Figure 4 The EDS spectrum shows that the material contains a large amount of Si, O, Ca and other elements, proving that the material contains a large amount of expanded perlite particles (1-1). As the amount of expanded perlite particles (1-1) in aggregate increases, the compressive strength and thermal conductivity of cement-based materials will gradually decrease. This is because the expanded perlite particles (1-1) have high porosity and low aggregate strength, which increases the pores inside the cement-based material and affects its strength. The low thermal conductivity and high porosity of the expanded perlite particles (1-1) can hinder heat transfer, further reducing the thermal conductivity of the cement-based material.

[0026] Figure 3This is a schematic diagram of an electron microscope magnification of nano-silicon dioxide in a new type of heat-insulating, anti-corrosion and self-repairing cement-based material for submarine tunnels in the implementation of the present invention. The nano-silicon dioxide (1-3) has an extremely small particle size with an average particle size of about 100 nm, which can fill the micro-pores and cracks in the cement-based material and reduce the channels for chloride ion penetration. In addition, the nano-silicon dioxide (1-3) can react with the calcium hydroxide released during the cement hydration process to generate more hydrated calcium silicate gel. The hydrated calcium silicate gel is the main binder in the cement-based material. When the amount of the hydrated calcium silicate gel increases, the microstructure is good and the porosity is low. It can refine the pore structure of cement-based materials, reducing large pores to micropores, which are not conducive to the migration of chloride ions. It can also improve the interface transition zone between cement paste and aggregate, enhance the density and strength of this area, thereby improving the cement-based material's resistance to chloride ion penetration. It also enhances the overall durability of cement-based materials, increases its density, improves the thermal insulation performance and compressive strength of cement-based materials, reduces thermal conductivity, and thereby improves the material's resistance to freeze-thaw cycles and sulfate erosion.

[0027] Figure 4 and Figure 5 They are respectively a schematic diagram of the distribution of each element in the EDS spectrum of a new type of heat-insulating, anti-corrosion and self-repairing cement-based material for submarine tunnels in the implementation of the present invention, and a total spectrum of the distribution of each element in the electron microscope of a new type of heat-insulating, anti-corrosion and self-repairing cement-based material for submarine tunnels in the implementation of the present invention. Figure 4 Cooperate Figure 5It can be seen that the material contains abundant C, N, and O elements that are stably dispersed inside. Combined with the previous cement-based material manufacturing process, it can be proved that the ion complexing agent triethanolamine (1-2) is stably dispersed in the cement-based material. The chemical formula of the ion complexing agent triethanolamine (1-2) is C6H15NO3, which can significantly promote the self-repair of cement paste cracks in a seawater environment. From the EDS energy spectrum, it can be seen that the new type of heat-insulating, anti-corrosion and self-repairing cement-based material disclosed in the present invention for submarine tunnels has Si, C, O, Ca and other elements uniformly distributed inside. In the cement-based material containing 1.5% ion complexing agent triethanolamine (1-2), cracks with an initial width of 400-600 μm can be completely self-repaired after being soaked in seawater for two days. The ion complexing agent triethanolamine (1-2) can quickly increase the alkalinity of the solution, increase the concentration of hydroxide ions, and interact with the high concentration of magnesium ions in seawater, causing magnesium hydroxide to quickly reach saturation and precipitate at the crack mouth, thereby quickly closing the crack. As the repair time increases, the magnesium ions in the seawater continue to diffuse into the cracks, the hydroxide ions in the matrix continue to be released, and magnesium hydroxide continues to form inside the cracks. At the same time, the carbon dioxide in the air dissolves in the seawater and migrates into the cracks, reacting with the calcium ions released from the matrix to form calcium carbonate precipitation. Ultimately, the self-healing products continue to accumulate in the cracks, forming a mixed product belt of magnesium hydroxide and calcium carbonate over 1 cm from the crack mouth to the depth of the crack, thus achieving the purpose of self-healing.

Claims

1. A new type of heat-insulating, anti-corrosion and self-repairing cement-based material for submarine tunnels, characterized by: A concrete schematic sample block (1) of a new type of heat-insulating, anti-corrosion and self-repairing cement-based material for an undersea tunnel is prepared by mixing expanded perlite particles (1-1), an ion complexing agent triethanolamine (1-2), nano silicon dioxide (1-3) and ordinary Portland cement (1-4) in a certain proportion and then casting them together; wherein the expanded perlite particles (1-1) maintain the temperature stability inside the undersea tunnel and reduce the influence of the external temperature on the inside of the cement-based material and the tunnel space; the ion complexing agent triethanolamine (1-2) is used to react with ions in the seabed to produce precipitates to achieve a self-repairing effect; the nano silicon dioxide (1-3), wherein the nano silicon dioxide (1-3) has a particle size of about 100 nm, is used to reduce chloride ion penetration; and the ordinary Portland cement (1-4) is used as a cementitious material.

2. The new type of heat-insulating, anti-corrosion and self-repairing cement-based material for submarine tunnels according to claim 1 is characterized by: The expanded perlite particles (1-1) are formed by preheating and roasting perlite ore. The expanded perlite particles are hydrophobic expanded perlite and have a thermal conductivity of about 0.0245 to 0.048 W / (m·K).

3. The new type of heat-insulating, anti-corrosion and self-repairing cement-based material for submarine tunnels according to claim 1 is characterized by: The ionic complexing agent triethanolamine (1-2) is an organic base that can increase the hydroxide ion concentration in the solution and thus promote the formation process of magnesium hydroxide, which can significantly improve the submarine self-healing performance of cement-based materials.

4. The new type of heat-insulating, anti-corrosion and self-repairing cement-based material for submarine tunnels according to claim 1 is characterized by: Nano-silicon dioxide (1-3) with a specific surface area greater than 600m 2 / g, which can fill the micropores and capillaries in cement-based materials, thereby reducing the porosity of cement-based materials, forming a denser and more uniform microstructure, and reducing the channels for chloride ion penetration; Nano-silica can react with calcium hydroxide produced during cement hydration to generate more hydrated calcium silicate gel; this is helpful to improve the density and impermeability of cement-based materials.

5. The new type of heat-insulating, anti-corrosion and self-repairing cement-based material for submarine tunnels according to claim 1 is characterized by: After optimization and adjustment, the proportion of each component in the material is as follows: the amount of expanded perlite particles (1-1) as aggregate is 90% of the weight of cement, the proportion of ion complexing agent triethanolamine (1-2) is 1.5% to 2%, the proportion of nano-silicon dioxide (1-3) is 2% to 8%, the water-cement ratio is 0.34, and the concrete strength is above C50, so as to ensure the thermal insulation, anti-corrosion and self-repairing properties of cement-based materials.

Citation Information

Cited By

  • Temperature-controlled anti-cracking, anti-corrosion and anti-rust waterproof material based on self-healing crystallization technology and preparation method thereof

    CN122853743A